RELATIONSHIP BETWEEN DIGITAL FUND TRANSFERS AND FINANCIAL PERFORMANCE OF EQUITY BANK, KAMPALA BRANCH; A DESCRIPTIVE, CORRELATIONAL AND CROSS-SECTIONAL STUDY. - David Mugabi; Murishid Kamya; Edmand Bakashaba (Student's Journal of Health Research, 2023)
Background This study aims to establish the relationship between digital fund transfers and the financial performance of Equity Bank, Kampala branch. Methodology 125 respondents were selected from a population of 144 participants. These were selected using purposive sampling techniques and simple random sampling. Primary data was collected using self-administered questionnaires, interviews, and Observation methods. Secondary data was obtained from annual reports, financial statements, meeting proceedings, Bank of Uganda publications, and the Uganda Bankers Association report  Results The findings also revealed a mean response to the statement "Digital fund transfer transaction takes long periods to be successful and the method is not user friendly for the uneducated hence less customer's trust which affects the revenue generated by the bank." 1.75 With a standard deviation of 0.45. Further, the findings revealed that 86.6% of the respondents disagreed with the statement. Therefore, digital fund transfer transaction does not take a long period to be successful and the method is user-friendly for the uneducated hence has more customer trust which improves the revenue generated by the bank. The financial performance of Equity Bank was 56.8% predicted by fund transfer (Adjusted R Square = 0.568). The remaining 43.2% was predicted by other factors outside the study. The regression model was also valid (sig.0.00 <.05). Therefore digital fund transfers significantly contribute to the financial performance of the bank by 56.8%. Conclusion The findings revealed a 0.423 correlation coefficient and a sig value of 0.000. This indicated a significant positive relationship between digital fund transfer and the financial performance of Equity Bank. Therefore, Equity Bank can improve its profitability by improving its digital fund transfers.  Recommendation The commercial bank should build customer trust in digital banking to stimulate its contribution to the growth, revenues, and profitability of the bank hence the financial performance of the bank.